Education, art and nature in William T. Harris and Manuel B. Cossío - Otero Urtaza, Eugenio (Historia y Memoria de la Educación, 2016)
William Torrey Harris (1835-1909) was an educator of great importance in the United States and can be seen as the link between the thought of Horace Mann and John Dewey. Harris met Giner and Cossío in Paris in 1889 and from that point on maintained a stable relationship with the Institución Libre de Enseñanza (Free Institution of Teaching, ILE). This allowed for an exchange of information and increased the knowledge in Spain of the pedagogical ideas that were being developed in his country. This paper looks at the first contacts between American pedagogy and the ILE, before walking us through Harris’ biography until he was appointed commissioner of education in the United States. We focus on his initial contact with transcendentalism and its subsequent connection with the thought of Hegel and on his wish to integrate all of these concepts into the idea of kindergarten as a fundamentally public space of coexistence for people of all groups and social classes. The core of the study offers a review of some similarities and differences between the thought of Harris and Cossío in connection with the educational potential of art and nature, especially regarding schools and technical training, concluding that both are part of a transnational trend in pedagogical thinking that goes beyond national frameworks. This «transatlantic community of discourse», as Kloppenberg called it, is a complex process of intellectual convergence that sought a middle way between idealism and positivism.